Magnetic Math Terhadap Kemampuan Berpikir Kritis Siswa Kelas VII - Difi Sutriani; Novi Susanti; Helni Indrayati (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to see the effect of the use of magnetic math teaching aids on the critical thinking skills of seventh grade students, the method used in the study is a quantitative method with a quasi-experimental design in the form of a nonequivalent control group design. Data collection techniques are carried out through documentation and critical thinking ability tests in the form of pre-test post-test without randomly selected samples. The results showed that the experimental class obtained 93,07% and the control class obtained 81,22% so that the results indicate that the use of magnetic math teaching aids has an effect on students' critical thinking skills on fraction material. The implications of this study indicate that magnetic math is able to improve students' critical thinking skills on fraction material. Thus, the use of magnetic math teaching aids can be used as an alternative learning media that helps students improve their critical thinking skills optimally.